Security and Trust Model Analysis for Banking System - Saini, Dinesh K.; Saini, Hemraj; Singh, Surjeet (International Journal of Sensors Wireless Communications and Control, 2021)
Background: There are mainly three types of banking includes Traditional banking, online banking, and mobile banking. The use of the latter two i.e, online banking and mobile banking, over traditional methods should rise exponentially among the people. This will be the implication only if the customers are made aware of the new technologies and advancements in the banking sector. Therefore, appropriate securities to be implied on the digital methods of banking for reliability and trust of the customers. Objective: In this paper, we formulate a model that represents a means for detecting and describing the transmission of malicious objects through various individual nodes in a server of banking. Methods: For a strong banking infrastructure, the challenge is to those concerned with information security to place a monetary value on the protection of information resources. In addition, a trust model for the banking system in online or offline modes is also provided. Results: The results of this model can help in understanding the mechanism by which malicious object spread, to predict the future course of an outbreak and to evaluate the strategies to control. Conclusion: The paper can be concluded to achieve its objective that how to maintain Trust in the banking system in different scenarios along with predicting the outbreak of a perticular malicious object.
Keywords: malicious object